Home » Blog » Multiplicative identity is its own multiplicative inverse

Multiplicative identity is its own multiplicative inverse

Prove that 1^{-1} = 1.


Proof. On the one hand since 1 is the multiplicative identity we have,

    \[   1 \cdot 1^{-1} = 1^{-1}.   \]

On the other hand, from Theorem I.10 (Exercise I.3.3, #1 part (d), we have (1^{-1})^{-1} = 1. Hence,

    \[   1^{-1} \cdot (1^{-1})^{-1} = 1 \qquad \implies \qquad 1^{-1} \cdot 1 = 1. \]

Therefore, since 1 \cdot 1^{-1} = 1^{-1} \cdot 1,

    \[   1 = 1^{-1}.   \qquad \blacksqaure\]

One comment

  1. Tiago says:

    Hi, RoRi. Your proof is of course correct; but I think there’s no need of using the reciprocal of the reciprocal. So, I will offer an alternative.

    You could simply say that:
    On the one hand, by Axiom 4, we know that 1 is the multiplicative identity, so 1 * (1^(-1)) = 1^(-1).
    On the other hand, by Theorem I.8. (and Axiom 6), we know that 1 * (1^(-1)) = 1 (definition of reciprocal).

    Therefore, you have 1^(-1) = 1 * (1^(-1)) = 1, i.e., 1^(-1) = 1.

    (P.S: Sorry, for not using LaTeX, I don’t know how to use it yet. I hope the answer is clear though)

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):